Effect of charcoal- enriched substrate on seedlings of rhizobium-inoculated legume trees - Cardoso, Irene Maria; Freitas, Aroldo Felipe de; Souza, Luiz Augusto Gomes de; Venturin, Nelson (Revista Árvore, 2016)
Native legume trees are planted in agroforestry systems for their hardiness and symbiosis with soil bacteria of the genus rhizobium, efficient in N2 fixation. The enrichment of the substrate composition with fine charcoal for seedling production of these trees is interesting for increasing soil porosity, water retention and the proliferation of beneficial microorganisms. Experiments were carried out to analyze the effect of substrate enrichment with charcoal on the quality of Clitoria fairchildiana, Enterolobium schomburgkii and Inga edulis seedlings. The treatments consisted of a 3:2:0.5 (v:v) mixture of clay soil, sand and bovine manure and a 3:2 (v:v) mixture of clay soil and sand combined with charcoal rates of 0, 10, 19 and 29%. After mixing the components, substrate samples were collected and chemically analyzed. The experiment was arranged in a completely randomized design with 5 treatments and 10 replications. The seedlings were inoculated with homologues rhizobia and growth controlled monthly. The plants were collected to determine the number of nodules and dry biomass of roots, shoots and nodules. Seedling growth was similar on substrates containing charcoal or manure, except for E. schomburkii, which increased by more than 100% on the charcoal-containing substrates. The number and dry biomass of nodules in the charcoal-containing substrates was up to 100% and 300% higher than in the manure-containing treatment, respectively. The results indicated that the substitution of manure by charcoal favors the seedling quality of the studied species.

O estabelecimento do plantio florestal com mudas bem noduladas favorece o seu crescimento inicial e sobrevivência após a fase de estabelecimento. As espécies leguminosas arbóreas ingá (Inga edulis), orelha-de-macaco (Enterolobium schomburgkii) e palheteira (Clitoria fairchildiana) têm sido recomendadas para recuperação de áreas degradadas e composição de sistemas agroflorestais pela sua rusticidade e capacidade de estabelecer simbiose com bactérias do solo do grupo dos rizóbios, eficientes em fixar N2. Foi conduzido estudo experimental para analisar o efeito da adição de carvão vegetal em mistura substrato sobre a qualidade de mudas produzidas em viveiro. Os tratamentos utilizados foram: mistura 3:2:0,5 (v:v) de solo argiloso, areia e esterco bovino e de solo argiloso e areia 3:2 (v:v), combinado com carvão vegetal em dosagem de 0, 10, 19 e 29 % de carvão em mistura. Amostras das misturas substratos foram coletadas e analisadas quimicamente. O delineamento foi o inteiramente casualizado com cinco tratamentos e dez repetições. As mudas foram inoculadas com estirpes homólogas de rizóbios, sendo que 5 mL planta-1 foram aplicados na base do coleto das mudas. O crescimento das mudas foi acompanhado mensalmente e as plantas foram coletadas para contagem do número de nódulos formados e determinação da biomassa das raízes, parte aérea e nódulos após secagem a 65ºC/72 h. O uso de esterco na composição dos substratos inibiu a nodulação em todas as três espécies estudadas. Foi também possível verificar aumento na qualidade das mudas pelo uso de carvão no substrato.
Keywords: Inga edulis; Enterolobium schomburgkii; Clitoria fairchildiana